Removal of arsenic compounds from water and wastewater using nano-sized iron - Bondarieva, A.I.; Kholodko, Yu.M.; Tobilko, V.Yu.; Kornilovych, B.Yu. (Reports of the National Academy of Sciences of Ukraine, 2021)
We have investigated the physicochemical properties of the removal of arsenic compounds from water and wastewater utilizing nanoscale iron deposited on the surface of clay minerals. It is found that the obtained materials have much better sorption properties in terms of arsenic removal from aqueous solutions compared to natural silicates. Kinetic data of sorption of arsenate ions by samples of stabilized nanoscale iron were analyzed using the pseudo-first-order and pseudo-second-order models. Kinetic studies show that the adsorption As(V) process is better described by the pseudo-second order model. The obtained results show that sorbents based on nanoscale iron effectively remove toxic arsenic ions from contaminated water.